Engaging complex temporalities in environmental rhetoric - Senda-Cook, Samantha; Endres, Danielle; Sowards, Stacey K.; McGreavy, Bridie (Frontiers in Communication, 2023)
In this essay, we identify a temporal turn in environmental rhetoric. As field researchers, we have experienced different senses of time bumping against one another in intercultural, ecological situations. Although these micro-experiences of time provide a constant grounding for our lives, we are also aware of the macro-expressions of time and the ways that they order our world and understanding of environmental degradation. We detail three interrelated temporal themes in environmental rhetoric. First, we delve into the practical considerations of time, articulating it in relation to how humans address environmental crises. Second, we respond back to ourselves by discussing epistemological concerns of time that emphasize knowing as critical to appropriate action and recognizing the need for impatience in the face of colonial, sexist, and racist systems that have existed for far too long. Lastly, we unpack multiple conceptualizations of time—the ontological commitments of different entities, systems, and cultures—and ask how scholars should conduct their own work given the temporal challenges presented by environmental problems, the demands of the field, the need for radical change, and the necessity of intelligent and meaningful choices. We do not seek to resolve tensions between these three themes but deepen the field’s engagement with multiple temporalities. The conclusion offers some pathways to stimulate further scholarship about environmental temporalities.